PENGEMBANGAN BAHAN AJAR HANDOUT BERBASIS BUDAYA BANTEN - Ela Suhaelah; Ana Nurhasanah; Zerri Rahman Hakim (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to find out stages in developing a handout based on Banten culture for teaching materials and the validity of the handout. This research utilized Research and Development (R&D) method by Sugiyono that consisted of 6 steps, namely: (1) problem analysis, (2) data collection, (3) product design, (4) design validation, (5) design revisions, and (6) product trial test. The development of the handout was carried out through the validation test by the material experts, media experts, and education experts. Then, to accomplished the limited trial test, a product trial test was conducted after the validation test involving 15 fourth-grade students at SDN Unyur as the research subjects. Findings of this research were that the percentage from the material experts was 95% with a very feasible category. Then, the result from the media expert obtained a percentage of 78% with feasible category. After that, the result from the education expert indicated that the percentage for the handout was 93% with very feasible category. Meanwhile, the results of the trials product obtained the percentage of 90% with very feasible category. Based on these results, it could be concluded that the handout based on Banten culture for the fourth-grade students at SDN Unyur was feasible to be used using as the teaching materials after going through the six stages of development procedures.